Pengaruh Model Pembelajaran Make a Match terhadap Kemampuan Berpartisipasi Siswa dalam Pembelajaran Bahasa Indonesia di Kelas 3 SDIT Cendekia - Pratiwi, Andita; Dzikrullah, Mochammad Fadhlan; Mustikaati, Wina; Nurhayati; Afiyah, Wardatul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the effect of the Make a Match learning model on students' ability to participate in Indonesian language subjects in grade 3 SDIT Cendekia. The research used descriptive qualitative method with observation technique and Learner Worksheet (LKPD), involving 22 students as samples. The results showed that the Make a Match model significantly increased students' participation in learning. Students' activeness in discussion, intergroup cooperation, and learning motivation experienced a positive increase. This model succeeded in creating an interactive, fun, and healthy competitive learning atmosphere through card-matching activities. Students are directly involved in the learning process, which encourages them to discuss more, ask questions, and share opinions. The conclusion of the research shows that the Make a Match model can be an effective alternative learning strategy to increase participation and quality of Indonesian language learning in elementary schools.